Judicial Formalism and Women’s Economic Rights After Divorce: A Feminist Legal Study of a Religious Court Decision - Umah, Rahma Khofifah Khoirun; maftukhin, Maftukhin (Islamic Family Law Study Program, Sharia Faculty, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Religious court adjudication in divorce cases in Indonesia continues to exhibit a strong reliance on judicial formalism, often at the expense of substantive gender justice. One manifestation of this tendency is the rejection of post-divorce economic claims by former wives, particularly in cases involving civil servant salaries. This study examines a Religious Court decision that denied a former wife’s claim to a one-third allocation of her ex-husband’s salary, despite her demonstrated economic vulnerability following divorce. The research aims to critically analyze the judicial reasoning underlying this rejection and to assess the extent to which women’s economic rights are accommodated within religious court practice from a Feminist Legal Theory perspective. Employing a normative juridical method, the study integrates a case-based and conceptual approach through an analysis of court decisions, statutory regulations, and feminist legal scholarship. The findings reveal that the judges’ reasoning is predominantly procedural and formalistic, focusing narrowly on the husband’s economic capacity while disregarding the wife’s non-monetary contributions during marriage, such as domestic and reproductive labor. This approach effectively marginalizes women’s lived experiences and reinforces gendered economic inequality after divorce. The study contributes to Islamic family law scholarship by demonstrating how judicial formalism can undermine the protective function of post-divorce economic rights. By applying Feminist Legal Theory as a critical analytical tool, this research highlights the need for a more substantive, gender-responsive interpretation of family law to ensure equitable outcomes for economically vulnerable women, particularly former wives of civil servants.